Triangulating Critical Reading: A Comparative Study of Written, Visual, and Oral Assessments in an EFL Context - Kamila, Fatima; Pelawi, Rinawati (Foremost Journal, 2025)
Critical reading is a vital skill for tertiary EFL learners, as it helps develop deeper understanding and analytical thinking. However, most assessment practices still rely heavily on paper-based tests that primarily measure comprehension in a limited way, leaving a gap in understanding how students demonstrate critical reading through alternative methods. This study investigates how tertiary-level EFL students demonstrate critical reading through three assessment formats: a written paper-based test, a visual concept map, and an oral BookTalk presentation. Drawing on descriptive data from ten English Literature students enrolled in a Critical Reading course, the study compares performance across these modalities to understand how each format supports different dimensions of critical reading. Findings show that while paper-based assessments effectively measure basic comprehension, visual and oral tasks better reveal skills such as synthesis, interpretation, and personal response. Students who performed moderately on written tests often improved significantly in the visual and oral tasks, suggesting that multimodal assessments better capture learners’ critical engagement. The results underscore the value of integrating varied assessment types to form a more comprehensive and equitable understanding of student learning. By including visual and oral formats, educators can support a wider range of learner strengths and foster deeper interaction with texts. This study contributes to expanding assessment practices in tertiary EFL contexts by highlighting the potential of alternative formats in developing students’ critical reading skills.